Analisis Faktor-faktor yang Memengaruhi Volume Pembelian Beras IR 64 di Kecamatan Trucuk, Kabupaten Klaten - Aryanto, Tri; Santoso, Siswanto Imam; Budiraharjo, Kustopo (Universitas Galuh, 2025)
Trucuk District has a heterogeneous socio-economic structure, with the majority of people working in the agriculture, trade, and service sectors. This condition has a direct influence on rice consumption patterns, especially in choosing the type of rice consumed. Therefore, an analysis of the factors that influence the volume of IR 64 rice purchases in this area is important to understand the dynamics of rice consumption and market needs in more depth. The purpose of this study was to analyze the factors that influence the volume of IR 64 rice purchases in Trucuk District, Klaten Regency and to determine the influence of each factor on the volume of IR 64 rice purchases. This study was conducted in December 2024 in Trucuk District, Klaten Regency. The research method used a survey method. The analysis method used multiple linear regression analysis. Based on the results of the study, the average rice purchase volume was 7.2 kg/month, the average income was IDR 1,499,000/month, and the price of rice ranged from IDR 14,000/kg to IDR 18,000/kg. Simultaneously, income, number of family members, and price affect the volume of IR 64 rice purchases. Based on partial results, it is known that income, number of family members, and price affect the volume of IR 64 rice purchases.